Pengaruh Fraud Triangle dan Komite Audit Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Property dan Real Estate Yang Terdaftar di BEI Periode 2020-2022 - Desta Eka Rahmadani; Yana Mustika; Syamsul Bahri (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the influence of the fraud triangle and audit committe on financial statement fraud in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The study seeks to understand the components of the fraud triangle, which include pressure, opportunity, rasionalization, as well as the role of the audit commite, which may act as factors influencing the occurrence of financial statement fraud. The research method used in quantitative analysis. The type of data used in this study is secondary data obtained from the companies’ annual reports, which can be downloaded from the website www.idx.co.id. The data collection technique in this study employed purposive sampling, resulting in a sample of 12 companies. The data analysis technique used are the T-test, F-test, and coefficient of determination. The results of this study indicate that the nature of industry has an impact on financial statement fraud. However, external pressure, rasionalizartion, and the audit committe do not have an influence on financial statement fraud. Meanwhile simultaneously, external pressure, nature of industry, rasionalization, and audit committee collectively influence financial statement fraud.